Free Field Representation and Form Factors of the Chiral Gross-Neveu Model - Britton, Stephen (Trinity College (Dublin, Ireland). School of Mathematics, 2013)
The process of using the free field representation to construct form factors of two dimensional integrable models is very promising. In this thesis, this procedure is analysed and adapted for application to the chiral Gross-Neveu model. The vertex operators and Zamolodchikov-Faddeev algebra for the particles are presented, with a similar structure producing a representation of the local operators of the theory. Using these techniques, the form factors of the model are then constructed as traces over the space of Zamolodchikov-Faddeev operators, and given in terms of an integral representation. In particular, the two-particle form factors of the current operator are found, and shown to agree with previous results in the literature.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin